PENINGKATAN KETERAMPILAN MENULIS CRITA CEKAK MELALUI METODE PEMBELAJARAN EXAMPLES NON-EXAMPLES DENGAN MEDIA GAMBAR BERSERI - Ari Fitri Fauziyyah; Raheni Suhita; Budhi Setiawan (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2019)
This classroom action research aimed to improve the students’ activeness and crita cekak writing skill using examples non-examples learning method with serial picture media in the 10th Social Science Graders of SMA Negeri 1 Sukoharjo. This classroom action research was conducted in two cycles, each of which consisting of planning, acting, observing, and reflecting. The subject of this study are 29 students in the class at X IPS 4 SMA Negeri 1 Sukoharjo. The data sources used were event, document, and informant. Techniques of collecting data used were observation, document analysis, interview, and task/test administration. Data validation was carried out using method and data source triangulations. Technique of analyzing data used was a descriptive comparative and critical analysis. The study shows that on the on pre-action the writing skill crita cekak only 27.58%. After the first cycle was done, 62.06% and  after the second cycle was done student who pass increased 89.65%.